A compact linearly polarized RLSA antenna integrated with circular ring resonator (CRR) for 5G mm-wave applications - Mohd Ibrahim, Imran; Alwareth, Husam Abdulqudos Ahmed; Al Gburi, Ahmed Jamal Abdullah; Zakaria, Zahriladha; A Majid, Huda; Purnamirza, Teddy (IOP Publishing Ltd, 2024)
This article introduces a compact linearly polarized (LP) radial line slot array antenna (RSLA) that incorporates a metamaterial of circular ring resonator (CRR) reflector for improving the bandwidth. Hence, this enables the antenna to operate at n257 (26.5–29.5), n258(24.25–27.5), and n261(27.5–28.35) frequency bands which are standardized by Federal Communications Commission (FCC) with a minor reduction of the directivity. Due to the short wavelength of the millimeter wave bands, the technique of the RLSA design has been advantageous for achieving high gain. The prototype of the RLSA antenna and the metamaterial CRR reflector are designed and fabricated at 28 GHz resonance frequency utilizing Rogers 5880 substrate and fed using an SSMA coaxial connector with an air gap cavity equivalent to half guide wavelength (λg/2) between substrate and ground plane. The method of integrating the CRR reflector with the LP-RLSA antenna delivered a passband transmission operating at (22–29.5) GHz. The proposed antenna has a similar agreement between simulated and measured for directivity and bandwidth. it achieved a peak directivity of 20 dB with a squinted main lobe at 12° and a fractional bandwidth of 29.13%. The fabricated RLSA antenna dimensions are 130 mm × 130 mm × 10.65 mm which is compact compared to conventional RLSA antennas.